2020
DOI: 10.1002/anie.201916520
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence for Metallic Cobalt Boosting CO2 Electroreduction on Pyridinic Nitrogen

Abstract: Nitrogen‐doped carbon materials (N‐Cmat) are emerging as low‐cost metal‐free electrocatalysts for the electrochemical CO2 reduction reaction (CO2RR), although the activities are still unsatisfactory and the genuine active site is still under debate. We demonstrate that the CO2RR to CO preferentially takes place on pyridinic N rather than pyrrolic N using phthalocyanine (Pc) and porphyrin with well‐defined N‐Cmat configurations as molecular model catalysts. Systematic experiments and theoretic calculations furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(80 citation statements)
references
References 41 publications
3
76
0
1
Order By: Relevance
“…Recently, researchers have used phthalocyanine (Pc) and porphyrin with a clear nitrogen-carbon configuration as the catalyst was analyzed by electrocatalysis experiment. [71][72] Through Raman spectrum characterization and TEM image analysis of the catalytic material, it was found that the structure of the metal phthalocyanine did not change before and after electrocatalytic carbon dioxide, and no CoÀ N bond was formed. It was observed by XPS that metal cobalt and phthalocyanine interacted and had good stability.…”
Section: Electrocatalytic Reduction Of Co 2 By Metal Phthalocyaninesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, researchers have used phthalocyanine (Pc) and porphyrin with a clear nitrogen-carbon configuration as the catalyst was analyzed by electrocatalysis experiment. [71][72] Through Raman spectrum characterization and TEM image analysis of the catalytic material, it was found that the structure of the metal phthalocyanine did not change before and after electrocatalytic carbon dioxide, and no CoÀ N bond was formed. It was observed by XPS that metal cobalt and phthalocyanine interacted and had good stability.…”
Section: Electrocatalytic Reduction Of Co 2 By Metal Phthalocyaninesmentioning
confidence: 99%
“…In this experiment, the catalytic active site for carbon dioxide reduction is Co(I), although the electronwithdrawing substituent (cyano) can reduce the nucleophilic 111, Pc and Co(111)@Pc at 0 V vs. RHE (the asterisk itself (*) denotes the adsorption site and * with species means surface-bound species). [71] Reproduced with permission from Ref. 71 ability of the Co(I) site, which may lead to a reduction in the binding capacity of carbon dioxide.…”
Section: Electrocatalytic Reduction Of Co 2 By Phthalocyanine and Cntmentioning
confidence: 99%
See 1 more Smart Citation
“…With different N-doping forms, the corresponding electrochemical CO 2 RR performance may exhibit a huge difference [24,25]. For instance, recent studies showed that pyridinic N atoms were more likely to adsorb CO 2 and serve as the favorable sites for CO 2 RR [26][27][28]. Accordingly, the CO 2 RR performances can be manipulated by regulating the component of the carbon materials.…”
Section: Plasma-regulated N-doped Carbon Nanotube Arrays For Efficienmentioning
confidence: 99%
“…Excessive carbon dioxide (CO 2 ) generated by combustion is discharged into the atmosphere, which seriously disrupts the original normal carbon cycle of nature, causing global warming, and then causes a series of serious environmental problems [1,2], such as sea level rise, land desertification, and climate abnormality. Therefore, the capture and conversion of CO 2 into fuel or chemical raw materials with high added value has become one of the hot spots of scientific research because it can provide solutions to carbon emissions and energy crisis at the same time [3][4][5][6][7][8]. In the past few decades, various technologies such as biochemical, electronic, photochemical, radiochemical, and thermochemical have been developed to reduce CO 2 [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%